Seventh-day Sabbath Observance and Cardiovascular Parameters: A Theological Analysis and Narrative Integrative Review of Epidemiological and Psychophysiological Evidence - Douglas Sepang; Grace Kaparang (MARAS : Jurnal Penelitian Multidisiplin, 2026)
Cardiovascular disease remains the leading cause of mortality worldwide, with psychosocial stress, neuroendocrine dysregulation, and unhealthy lifestyle behaviors contributing significantly to its development. Seventh-day Adventist (SDA) populations provide a unique natural model for examining the relationship between structured weekly Sabbath observance and cardiovascular health. This study synthesized epidemiological, psychophysiological, and chronobiological evidence regarding the association between Seventh-day Sabbath observance and cardiovascular parameters through a theological analysis and narrative integrative review of peer-reviewed studies involving SDA populations, Sabbath observance, stress biomarkers, and circaseptan rhythms. The findings indicate that Sabbath observance promotes holistic well-being by integrating physical, mental, social, spiritual, and moral dimensions of life. Evidence consistently shows that SDA populations exhibit lower blood pressure, reduced serum cholesterol levels, and decreased cardiovascular disease risk compared with non-SDA populations. Experimental studies also report lower cortisol levels following Sabbath observance, suggesting reduced hypothalamic–pituitary–adrenal axis activation. Overall, structured weekly rest may contribute to cardiovascular protection through interconnected behavioral, psychosocial, neuroendocrine, and chronobiological mechanisms. Further longitudinal and experimental studies are needed to clarify the physiological effects specifically attributable to Sabbath observance.